Pharmacokinetic, Metabolism, and Metabolomic Strategies Provide Deep Insight Into the Underlying Mechanism of Ginkgo biloba Flavonoids in the Treatment of Cardiovascular Disease - Tao, Yi; Zhu, Fei; Pan, Meiling; Liu, Qing; Wang, Ping (Frontiers in Nutrition, 2022)
Ginkgo biloba, known as the "living fossil", has a long history of being used as botanical drug for treating cardiovascular diseases and the content of flavonoids as high as 24%. More than 110 different kinds of flavonoids and their derivatives have been separated from Ginkgo biloba, including flavones, flavonols, biflavonoids, catechins and their glycosides, etc., all of which display the ability to dilate blood vessels, regulate blood lipids, and antagonize platelet activating factor, and protect against ischemic damage. At present, many types of preparations based on Ginkgo biloba extract or the bioactive flavonoids of it have been developed, which are mostly used for the treatment of cardiovascular diseases. We herein review recent progress in understanding the metabolic regulatory processes and gene regulation of cellular metabolism in cardiovascular diseases of Ginkgo biloba flavonoids. First, we present the cardioprotective flavonoids of Ginkgo biloba and their possible pharmacological mechanism. Then, it is the pharmacokinetic and liver and gut microbial metabolism pathways that enable the flavonoids to reach the target organ to exert effect that is analyzed. In the end, we review the possible endogenous pathways toward restoring lipid metabolism and energy metabolism as well as detail novel metabolomic methods for probing the cardioprotective effect of flavonoids of Ginkgo biloba.